1961
DOI: 10.4039/ent93867-10
|View full text |Cite
|
Sign up to set email alerts
|

Variation Between Samples of Immature Stages, and of Mortalities from Some Factors, of the European Corn Borer, Ostrinia nubilalis (Hübner) (Lepidoptera: Pyralidae), on Sweet Corn in Quebec

Abstract: This is a report on a program to sample the European corn borer, Ostrinia nubilalis (Hbn.), with the object of obtaining reliable statistics for life tables (see e.g. Morris, 1955; LeRoux and Reimer, 1959).Basic studies on factors determining abundance of the European corn borer are few, some of the most notable having been carried out by Barber (1926), Huber et al. (1928), Thompson and Parker (1928), Stirrett (1938), Vance (1943), Baker et al. (1949), Bigger and Petty (1953), Everett et al. (1958) and Chiang … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1961
1961
1988
1988

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…In the present smdy it was found that the amount of sampling required for a specified percentage error decreased as total crop or crop damages from all sources increased. Similar observations were also made in related studies on insect population counts (LeRoux and Reimer 1959;Hudon and LeRoux, 1961). Considering that the sampling plan outlined in Table VIII results from very low figures for total crop and crop damages from all sources it is very likely that the number of trees to be sampled for higher values of total crop and crop damages would be lower than those recommended here.…”
Section: Suggested Sampling Plansupporting
confidence: 84%
“…In the present smdy it was found that the amount of sampling required for a specified percentage error decreased as total crop or crop damages from all sources increased. Similar observations were also made in related studies on insect population counts (LeRoux and Reimer 1959;Hudon and LeRoux, 1961). Considering that the sampling plan outlined in Table VIII results from very low figures for total crop and crop damages from all sources it is very likely that the number of trees to be sampled for higher values of total crop and crop damages would be lower than those recommended here.…”
Section: Suggested Sampling Plansupporting
confidence: 84%
“…Reviews by Brindley and Dicke (1963) and Brindley et al (1975) concluded that although natural enemies can reduce corn borer populations significantly in some locations or years, they cannot be depended upon over 5 years at any given site, and their effect is frequently minimal. A comprehensive 7-year life-table study in Quebec (Leroux et al 1963;Hudon and Leroux 1961) attributed greatest mortality to migration of moths and dispersal of larvae out of test plots.…”
Section: October 1988mentioning
confidence: 99%
“…Observations made on the relationship existing between the number of samples needed for a given precision and population densities of the species studied by LeRoux and Reimer (1959), LeRoux (1961), and Hudon and LeRoux (1961) are applic2ble here since populations of A. argyrospilus are generally of the negative binomial type distribution.…”
Section: Sampling Considerationsmentioning
confidence: 99%